Rapid Characterization of the February 2023 Kahramanmaraş, Türkiye, Earthquake Sequence - Goldberg, Dara E.; Taymaz, Tuncay; Reitman, Nadine G.; Hatem, Alexandra E.; Yolsal-Cevikbilen, Seda; Barnhart, William D.; Irmak, Tahir Serkan; Wald, David J.; Ocalan, Taylan; Yeck, William L.; Ozkan, Berkan; Jobe, Jessica A. Thompson; et al. (SEISMOLOGICAL SOC AMER, 2023)
The 6 February 2023 Mw 7.8 Pazarc & imath;k and subsequent Mw 7.5 Elbistan earthquakes generated strong ground shaking that resulted in catastrophic human and economic loss across south-central T & uuml;rkiye and northwest Syria. The rapid characterization of the earthquakes, including their location, size, fault geometries, and slip kinematics, is critical to estimate the impact of significant seismic events. The U.S. Geological Survey National Earthquake Information Center (NEIC) provides real-time monitoring of earthquakes globally, including rapid source characterization and impact estimates. Here, we describe the seismic characterization products generated and made available by the NEIC over the two weeks following the start of the earthquake sequence in southeast T & uuml;rkiye, their evolution, and how they inform our understanding of regional seismotectonics and hazards. The kinematics of rupture for the two earthquakes was complex, involving multiple fault segments. Therefore, incorporating observations from rupture mapping was critical for characterizing these events. Dense local datasets facilitated robust source characterization and impact assessment once these observations were obtained and converted to NEIC product input formats. We discuss how we may improve the timeliness of NEIC products for rapid assessment of future seismic hazards, particularly in the case of complex ruptures.
Keywords: INVERSION; CALIFORNIA; TURKEY; Geochemistry & Geophysics